How Taxes and Budget Deficits Determine Domestic Product - Fritz Helmedag (Wirtschaftsdienst)
Abstract In theory and practice, the opinion predominates that tax cuts stimulate economic activity. But possible contractionary repercussions due to public spending that falls with tax receipts is not discussed. As part of an elementary macroeconomic analysis, the first step is to examine how varying tax returns and alternative budget reactions influence national income. Well-established recipes for boosting aggregate demand turn out to be counterproductive. The critique that government expenditures on credit can never be self-financing is also untenable as the objection rests on an abridged deficit multiplier. However, the desired economic stimulus will be paralyzed if the extra tax yield is used to repay debt. Disposable private income depends on the effective budget deficit but not on the tax rate, although it affects the share of public goods in domestic product. Guidelines for a welfare-oriented debt management complete the recommendations for a functional fiscal policy.